1986
DOI: 10.1002/jcp.1041270206
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids stimulate the release of superoxide by neutrophils and change their morphology

Abstract: All-trans-retinal stimulated the release of superoxide by human and guinea pig neutrophils 63 +/- 14 SD and 53 +/- 5 SD nmol of O2-/min/10(7) cells, respectively. Superoxide release by unstimulated cells was negligible. All-trans-retinal also induced morphological changes (i.e., evaginations) in these cells. Other retinoids were effective in instigating these phenomena. The similarities of these effects to those instigated by cis-unsaturated fatty acids (Badwey, J.A., et al., 1984, J. Biol. Chem., 259:7870-787… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 44 publications
4
51
2
Order By: Relevance
“…These are similar in appearance to the blebs described in cultured cells in response to a variety of influences that induce oxidant stress. 2 " 6 In these cultured preparations, the lesions were ascribed to oxidation of thiols with consequent alterations in the cytoskeleton of the cells. 7 Vascular smooth muscle in cerebral arterioles exposed to H 2 O 2 also showed evidences of damage consisting of vacuolization or the appearance of electron-dense inclusion bodies.…”
mentioning
confidence: 99%
“…These are similar in appearance to the blebs described in cultured cells in response to a variety of influences that induce oxidant stress. 2 " 6 In these cultured preparations, the lesions were ascribed to oxidation of thiols with consequent alterations in the cytoskeleton of the cells. 7 Vascular smooth muscle in cerebral arterioles exposed to H 2 O 2 also showed evidences of damage consisting of vacuolization or the appearance of electron-dense inclusion bodies.…”
mentioning
confidence: 99%
“…Retinoids do not only inhibit but also stimulate PKC in vitro under certain experimental conditions [13,14,23]. In addition, retinoids were reported to activate NADPH oxidase in neutrophils [24]. We found that retinoic acid and retinal did not induce 02 -formation in HL-60 cells (data not shown).…”
Section: Discussionmentioning
confidence: 70%
“…Table 2 shows that AACOCF $ inhibited neither the fMLP-nor the PMA-induced free-radical generation, even at 60 µM, where the drug abolished the AA release triggered by either stimulus (Table 1). This result was rather surprising since exogenously applied AA is a well-known stimulator of the oxidase [42,43], and non-selective blockers of PLA # (like bromophenacyl bromide) can completely suppress superoxide generation [23,44]. These earlier findings lent credence to the assumption that endogenous AA production is mandatory for oxidase activation [45].…”
Section: Does Aacocf 3 Influence Nadph Oxidase or Other Ph-regulatorymentioning
confidence: 96%